Ventilatory variables are strong prognostic markers in elderly patients with heart failure. Issue 3 (1st September 2002) - Mejhert, M; Linder-Klingsell, E; Edner, M; Kahan, T; Persson, H
Abstract : Objective: To evaluate the safety and prognostic capacity of cardiopulmonary exercise testing in patients ≥ 60 years old who are hospitalised with heart failure caused by left ventricular dysfunction. Design: Prospective study. Setting: University hospital. Patients: Study participants were 67 patients (66% men) with clinical heart failure stabilised on medical treatment. The study is a part of a nursing intervention study. Mean (SD) age was 74 (6) years, New York Heart Association functional class II–III, and ejection fraction 0.36 (0.11). Interventions: Cardiopulmonary exercise testing and echocardiography. Main outcome measures: Peak oxygen consumption (V̇o 2 ), peak ventilatory equivalents for carbon dioxide (V̇E/V̇co 2 ) and oxygen (V̇E/V̇o 2 ), left ventricular volumes, and mortality. Results: Mean (SD) peak V̇o 2 was 11.7 (3.7) ml/kg/min, peak V̇E/V̇co 2 43 (9), and peak V̇E/V̇o 2 46 (11). During 12–59 months of follow up, 14 patients died. In univariate analyses peak V̇o 2, V̇E/V̇o 2, and V̇E/V̇co 2 were all strongly related (p < 0.01) to mortality. In a multivariate Cox regression analysis, peak V̇E/V̇co 2 was the strongest predictor of mortality (p < 0.001), followed by left ventricular end systolic volume (p < 0.001). A cut off of peak V̇E/V̇co 2 at ≥ 45 gave a univariate hazard ratio of 6.7 for death during follow up. No adverse events occurred during the exercise test. Conclusion: These findings extend results found in selected middle aged patients to elderly patients with heart failure and show that ventilatory parameters from a cardiopulmonary exercise test, such as peak V̇o 2, V̇E/V̇o 2, and V̇E/V̇co 2 are powerful predictors of mortality.